(3GdETGQGJ Edi HjGf GdCSeGA GdeHgeGJs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3GdNWjH GdHZOGOj , CHh HcQ CMeO Hf Ydj Hf KGHJ GdNWjH GdHZOGOj,J (B463 (3g` s
(3ChdgG (B:s
(3GdMeO ddg HGQF GdeUfhYGJ heOHQ GdeMOKGJ heUQa GdCdSf hGddZGJ GdN CeG HYO , aEf Yde GdMOjK ef GfaS GdYdhe s
(3BNQgG (B:s
(3Ke CHhHcQ CMeO Hf Ydi Hf KGHJ GdNWjH GdHZOGOi agPG BNQ eG JjSQ hGdMeO ddg s
(3GNJUQ ajg cJGH GdNWjH GdHZOGOi GdeSei GdCSeGA GdeHgeI ai GdCfHGA GdeMceIs
(3GfXQ GdbSe GdChd ef GdJGQjN Qbe (B37s
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs